DEVELOPMENT OF THE REFLECTIVE COMPONENT OF ENGINEERING COMPETENCE OF UNIVERSITY STUDENTS WHEN STUDYING MATHEMATICS - Lozovaia N. A. (Engineering education in the conditions of digitalization of society and economy, 2023)
The work updates the role of reflection in the engineering training of students. The methods and means of developing the reflective component in the professional training of future engineers when studying mathematics in the conditions of digitalization of education and the strengthening of the role of independent work of students are considered.
Keywords: студент; проект; project; самостоятельная работа; рефлексия; математическая подготовка; инженерная компетентность; engineering competence; reflection; independent work; student; mathematical preparation